Diagnostic value of the apparent diffusion coefficient in differentiating malignant from benign endometrial lesions - Scepanovic, Bojana; Andjelic, Nikola; Mladenovic-Segedi, Ljiljana; Kozic, Dusko; Vuleta, Dusan; Molnar, Una; Nikolic, Olivera (Frontiers in Oncology, 2023)
Introduction Magnetic resonance imaging (MRI) with its innovative techniques, such as diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC), increases the diagnostic accuracy in distinguishing between malignant and benign lesions of the endometrium. The aim of the study was MRI differentiation between malignant and benign endometrial lesions and correlation with histopathological findings with a special emphasis on quantitative analysis. An additional aim was to correlate the ADC values and histological tumor grades. Methods The prospective study included 119 female patients with or without vaginal bleeding and pathological values of endometrial thickness, who underwent MRI examinations. According to MRI reports the patients were divided into 45 suspicious malignant and 74 suspicious benign endometrial lesions. The radiological diagnosis was compared to the histopathological evaluation, which confirmed 37 malignant lesions while the rest were benign. Results The mean ADC value for malignant lesions was 0.761 ± 0.13×10−3 mm2/s and for benign lesions was 1.318 ± 0.20×10−3 mm2/s. The ADC values for malignant lesions were expectedly lower than those of benign lesions (p<0.001). The ADC cut-off value was 1.007×10−3 mm2/s with a sensitivity of 100%, specificity of 92.7%, a positive predictive value of 60.3%, and a negative predictive value of 100%. In comparison with the histopathological findings, the sensitivity of MRI was 100%, specificity 90.2%, positive predictive value was 82.2%, and negative predictive value was 100%. Observing the histological grades 1, 2, and 3 of endometrial carcinoma, no statistically significant differences of mean ADC values were found. The mean ADC values for histological tumor grades 1,2 and 3 were 0.803 ± 0.13×10−3 mm2/s, 0.754 ± 0.12×10−3 mm2/s and 0.728 ± 0.13×10−3 mm2/s, respectively. Conclusion DWI and ADC values represent clinically useful tools for the differentiation between malignant and benign endometrial lesions with high sensitivity and good specificity, but the results failed to demonstrate their usefulness in differentiating histological grades of endometrial cancer.